2019
DOI: 10.1108/ecam-05-2018-0191
|View full text |Cite
|
Sign up to set email alerts
|

Construction worker productivity in hot and humid weather conditions

Abstract: Purpose The purpose of this paper shows the effect of hot and humid weather conditions (HHWCs) on workers that has resulted in considerable loss in the construction industry, especially during the hottest periods due to decline in worker productivity (WP). Until the last few decades, there is very limited research on construction WP in HHWCs. Nevertheless, these studies have sparked interests on seeking for the most appropriate methods to assess the impact of HHWCs on construction workers. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…In this study, the temperature is selected as the most important parameters. Previous research also mentioned the importance of the temperature in enhancing safety management [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. High temperature can cause heat rash, heat exhaustion, and heatstroke in construction workers [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the temperature is selected as the most important parameters. Previous research also mentioned the importance of the temperature in enhancing safety management [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. High temperature can cause heat rash, heat exhaustion, and heatstroke in construction workers [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature in winter also can cause fatigue, lumbago, and cold finger sensation [6]. Rameezdeen and Elmualim (2017) insisted that heat stress causes heat rash, heat cramp, heat fainting, heat exhaustion and heatstroke in construction workers [4], Mohammed et al (2019) noted how productivity losses, illnesses and injuries to workers may arise due to hot and humid weather conditions [13]. In addition, Yi and Chan (2013) found that hot and humid weather conditions caused worker fatigue and productivity losses, and they proposed an evaluation of heat stress to provide a proper balance between work and rest [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…subtropical regions. Hazardous environmental and work-related conditions disrupt workers' health and safety (HS) (Choudhry, 2017;Cheng et al, 2012;Shirali et al, 2016) and consequently their productivity and overall performance (Moohialdin et al, 2019;Zander et al, 2018;Li et al, 2016b). Hence, the effects of HHCs have received more attention and become a topic of significant concern for scholars and practitioners (Yang and Chan, 2017).…”
Section: Introductionmentioning
confidence: 99%